2021
DOI: 10.1186/s12913-021-06555-5
|View full text |Cite
|
Sign up to set email alerts
|

Holding the frontline: a cross-sectional survey of emergency department staff well-being and psychological distress in the course of the COVID-19 outbreak

Abstract: Background The coronavirus disease 2019 (COVID-19) outbreak has been associated with stress and challenges for healthcare professionals, especially for those working in the front-line of treating COVID-19 patients. This study aimed to: 1) assess changes in well-being and perceived stress symptoms of Dutch emergency department (ED) staff in the course of the first COVID-19 wave, and 2) assess and explore stressors experienced by ED staff since the COVID-19 outbreak. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…Similar to other studies, our analyses found that self-reported perceived stress correlated significantly with psychopathology [ 36 , 37 ], suggesting that nurses who perceived a high level of stress also perceived more symptoms of anxiety and depression. Remarkably, the levels of wellbeing among nurses during COVID-19, were even lower than among patients in the Spanish community mental health setting [ 21 ], and were lower than previous studies among nurses before and during COVID-19 [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 64%
“…Similar to other studies, our analyses found that self-reported perceived stress correlated significantly with psychopathology [ 36 , 37 ], suggesting that nurses who perceived a high level of stress also perceived more symptoms of anxiety and depression. Remarkably, the levels of wellbeing among nurses during COVID-19, were even lower than among patients in the Spanish community mental health setting [ 21 ], and were lower than previous studies among nurses before and during COVID-19 [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 64%
“…Moral distress has been a prominent theme for healthcare workers during the pandemic. [134][135][136][137] In a study in the Netherlands, two sources of moral distress that increased in COVID-19 (scarcity of resources and the perception of colleagues acting unsafely) were significant predictors of burnout. 103 In a Toronto hospital, moral distress was strongly related to emotional exhaustion and accounted for most of the difference in burnout between roles (nurses vs. other health professionals vs. other staff with regular patient contact; Hunter J, personal communication).…”
Section: Moral Distressmentioning
confidence: 99%
“…With regards to gender, inconsistencies also exist with no gender differences observed among Canadian resident physicians [ 19 ], U.S. medical students, interview candidates for residency, and internal medicine residents plus faculty [ 20 ], as well as Dutch emergency department staff during the first COVID-19 wave [ 21 ]. In contrast, well-being was noted to be lower among female paramedics and emergency physicians in Germany [ 16 ].…”
Section: Introductionmentioning
confidence: 99%